En los vértices de sombra: la araña en dos cuentos mexicanos - Vélez García, Juan Ramón (Amaltea. Journal of Myth Criticism, 2010)
The aim of this work is to study in two Mexican tales (“La migala” by Juan José Arreola and “La araña” by Guadalupe Dueñas) the teratological embodiment of anguish through an animal traditionally linked to nastiness and phobia: the spider. Both texts can be inserted into a current of writings which deal with the ambiguous projection of the state of mind, fears and obsessions in obstinate animal figures, such as “The raven” by Poe, “La mariposa negra” by Nicomedes Pastor Díaz, “Como abeja revolante” by Eulogio Florentino Sanz, “La mariposa” by Atilio Manuel Chiáppori, “A mi buitre” by Unamuno or “Obsesión” by Dámaso Alonso, to name a few. The analysis will focus on the particularities of the two main examples as well as on pertinent relations to other texts and traceable mythological resonances.